Taglusan Balibago, Angeles Learning Commons and Public Library - Gutierrez, Christian Dave V.; Tabafunda, Enrico B. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
When the average individual thinks of a library, they may picture vast halls filled with shelves after shelves of books. To some, there is nothing more intimidating than standing in the deafening silence amidst the cavernous interiors of these temples to learning. But such an image, regardless of accuracy, is now an outdated relic of the past. The Contemporary Library is more than just a glorified book lending service. In recent years, there have been a push to lessen the emphasis on collections and instead provide spaces for community development and skills learning in public libraries. Gone are the days of the stuffy, silent cathedral to higher learning ; libraries these days are more about the stories we share, and the bonds we forge. Taglusan : The Balibago, Angeles Learning Commons and Public Library is the product of such ideals. Aiming to provide spaces that improve the experience of its users while also providing the means for self improvement through learning ; Taglusan is an optimistic look at the future of library design in the country, creating for their patrons a more multi-level environment for learning and pleasure.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Public libraries -- Pampanga -- Philippines